Correlation of Traits Afffecting Grain Yield in Winter Maize (Zea mays L.) Genotypes - Poudel, M.; Paudel, H.K.; Yadav, B.P. (International Journal of Applied Sciences and Biotechnology, 2015)
The research was conducted under RCBD with three replication to study the inter relationships among traits affecting yield and its affecting character at National Maize Research Programme (NMRP), Rampur, Nepal in 2013. The eleven inbreeds line of maize variety at winter season in 2013 were evaluated for estimation yield and its affecting character. For efficient selection of grain yield, it is necessary to know relation of yield of maize and its morphological traits which are influencing on the grain yield. One of the objectives of this paper was to determine interrelationship between traits and the yields. Correlation coefficients among traits showed that yield was positively and highly significantly related with number of kernel rows per ear (0.788), number of kernels per row(0.571), ear girth(0.516), plant height(0.498), hundreds kernels weights(0.444) and significantly related with other character. .Number of Kernels rows per ear, number of kernels per row, plant height could be the important selection criteria in improving open pollinated maize varieties for high grain yield. Int J Appl Sci Biotechnol, Vol 3(3): 443-445